Persepsi Motivasi Kerja Karyawan di Le Grande Hotel Kabupaten Badung Bali - Suriyani, Ni Nyoman Ayu; Sudirman, I Made; Endrayani (Jurnal Mosaik Hospitaliti, 2024)
The hospitality industry can motivate employees to work well in managing human resources. Work motivation is divided into 2 main forms felt by employees, namely internal motivation and external motivation. This study aims to measure employee perceptions of intrinsic and extrinsic motivation. This research is located at Le Grande Hotel, Badung Regency, Bali. Data collection techniques in this study used observation and questionnaires. The sample size of this study was 52 employees and analyzed using quantitative analysis with SPSS software. The results show that employee perceptions in terms of intrinsic motivation are dominated by indicators of success that employees get while working. Then in terms of extrinsic motivation, it is dominated by indicators of supervision carried out to employees. With these results, it is hoped that human resource management in the hotel industry can properly manage employee motivation while working at the hotel. This is necessary to continue to be able to improve employee satisfaction and the quality of service provided to tourists who stay overnight.